Emergency Physicians' Preparedness for CBRNE Incidents in Hong Kong. Issue 2 (March 2013) - Hung, KKC; Lam, ECC; Wong, MCS; Wong, TW; Chan, EYY; Graham, CA
Background: Recent terrorist attacks with biological and chemical weapons have caused much concern for the public. The purpose of this study was to assess emergency doctors' preparedness in handling Chemical, Biological, Radiological, Nuclear and Explosive (CBRNE) incidents. Methods: This is a cross sectional survey of all emergency doctors working in public emergency departments (ED) in Hong Kong. Apart from the experience and confidence to handle these events, data on participants' willingness to participate in CBRNE incidents and training motivations were also analysed. Results: Biological and radiological events were found to be the least commonly encountered. Few respondents reported they were confident to manage biological events (10.6% to 29.8%), despite 66% of respondents reported having prior training in CBRNE management. Conclusions: This study demonstrates ED doctors' low confidence in managing specific CBRNE incidents. Current strengths identified include the good awareness of hospital emergency plans and high motivation to get more training.